Mechanical analysis of fiber-reinforced plastics using an elastoplastic-damage constitutive equation considering asymmetric material behavior. (15th September 2021) - Jang, Jinhyeok; Jeon, Seung-Yeol; Choi, Jae-Hyuk; Shim, Wonbo; Cho, Jeong-Min; Yoon, Sang-Jae; Choi, Chi-Hoon; Yu, Woong-Ryeol
Abstract: Mechanical modeling of fiber-reinforced plastics to predict nonlinear mechanical behavior along the off-axis direction is very complex due to tension–compression asymmetry. This study aimed aims to develop a generalized constitutive model for different types of unidirectional and woven composites, considering tension–compression asymmetry in various deformation ranges from elastic to plastic, and finally to failure. To capture the asymmetry effectively, a new multivariable plastic model was proposed with additional dilatational components and different elastic moduli for tension and compression. Finally, asymmetric failure criteria and a damage evolution law were introduced for strength prediction. The proposed model was implemented in a finite element analysis software via a user material subroutine, and experimentally validated in terms of off-axis tension and compression tests in various loading directions. The experimental results were accurately predicted using a multi-parameter plastic model in this study compared to previous other models with few parameters.